Intermittent theta burst stimulation to the left dorsolateral prefrontal cortex improves working memory of subjects with methamphetamine use disorder - Zhang, Yi; Ku, Yixuan; Sun, Junfeng; Daskalakis, Zafiris J.; Yuan, Ti-Fei (Psychological medicine, 2023)
Repetitive transcranial magnetic stimulation has been employed to treat drug dependence, reduce drug use and improve cognition. The aim of the study was to analyze the effectiveness of intermittent theta-burst stimulation (iTBS) on cognition in individuals with methamphetamine use disorder (MUD). This was a secondary analysis of 40 MUD subjects receiving left dorsolateral prefrontal cortex (L-DLPFC) iTBS or sham iTBS for 20 times over 10 days (twice-daily). Changes in working memory (WM) accuracy, reaction time, and sensitivity index were analyzed before and after active and sham rTMS treatment. Resting-state EEG was also acquired to identify potential biological changes that may relate to any cognitive improvement. The results showed that iTBS increased WM accuracy and discrimination ability, and improved reaction time relative to sham iTBS. iTBS also reduced resting-state delta power over the left prefrontal region. This reduction in resting-state delta power correlated with the changes in WM. Prefrontal iTBS may enhance WM performance in MUD subjects. iTBS induced resting EEG changes raising the possibility that such findings may represent a biological target of iTBS treatment response.